Relationship violence victimization and binge drinking trajectories among a nationally representative sample of adolescents. (9th May 2017) - Walsh, Kate; Moreland, Angela M.; Hanson, Rochelle F.; Resnick, Heidi S.; Saunders, Benjamin E.; Kilpatrick, Dean G.
ABSTRACT: The present study evaluated the impact of relationship violence (RV) victimization on the longitudinal trajectory of binge drinking (BD) among 3614 US adolescents (51.2% male) who participated in an initial telephone interview regarding physical and sexual RV victimization and binge drinking. Two follow‐up phone interviews were completed over approximately three years. Multilevel modeling revealed small, but significant, increases in BD over time; older adolescents and those who had ever experienced RV victimization were more likely to report BD at Wave 1 compared to younger adolescents and non‐victims. Although new RV victimization reported during the study predicted an increase in the likelihood of BD at that occasion, those who had ever experienced RV victimization were less likely to report BD over time compared to non‐victims. Contrary to expectations, no sex differences emerged. Findings indicate that BD may precede RV. Interventions to reduce alcohol‐related RV may be especially useful in this population.